Formal incentive systems in organization with a Swedish management style: conflict or interaction? - Cäker, Mikael; Andersson, Thomas; Wickelgren, Mikael (Proceedings of Pragmatic Constructivism, 2011)
The aim of our study is to explore how organizations that are typically characterized as under a Swedish management style relate to the trend of increased use of formal incentive systems. Interview-based case studies of two organizations with management principles strongly rooted in Swedish culture. Both organizations operate in industries strongly influenced by external pressure, which includes the discourse of incentive systems as a modern feature of management. Our results point at companies under a Swedish management systems recoqnizes the intrustion of incentive systems, but try to align with their own ideas about management as far as possible. A broad perspective on employee motivation, with a focus on career planning and development take a central role. On a strategic level, these organization tries avoid conflicts between the ideas of incentive systems and their existing management ideas in everyday management activity, by taking an explicit stand on a high organizational level. Further consideration of how incentive systems aligns with existing management ideas is needed. The well documented negative effects of incentive systems on employee relations can be avoided through active choices concerning how to implement incentive systems. Contributes to our understanding of how ideas of incentive systems interact with management ideas that builds on trust and open communication.